Phylogenetic identification and population differentiation of bottlenose dolphins (Tursiops spp.) in Melanesia, as revealed by mitochondrial DNA. Issue 3 (2nd April 2015) - Oremus, Marc; Garrigue, Claire; Tezanos‐Pinto, Gabriela; Scott Baker, C.
Abstract The taxonomic status of many dolphin populations remains uncertain in poorly studied regions of the world's ocean. Here we attempt to clarify the phylogenetic identity of two distinct forms of bottlenose dolphins (Tursiops spp.) described in the Melanesian region of the Pacific Ocean. Mitochondrial DNA control region sequences from samples collected in New Caledonia (n = 88) and the Solomon Islands (n = 19) were compared to previously published sequences of Tursiops spp., representing four phylogenetic units currently recognized within the genus. Phylogenetic reconstructions confirm that the smaller coastal form in Melanesia belongs to the same phylogenetic unit as T. aduncus populations in the Pacific, but differs from T. aduncus in Africa, and that the larger more oceanic form belongs to the species T. truncatus. Analyses of population diversity reveal high levels of regional population structuring among the two forms, with contrasting levels of diversity. From a conservation perspective, genetic isolation of T. aduncus in the Solomon Islands raises further concern about recent impacts of the commercial, live‐capture export industry. Furthermore, the low level of mtDNA diversity in T. aduncus of New Caledonia suggests a recent population bottleneck or founder effect and isolation. This raises concerns for the conservation status of these local populations.